En fallstudie av uppföljningsarbetet hos mark- och trädgårdsanläggningsföretag - Åberg, Olof (SLU/Dept. of People and Society, 2009)
This study was made to compare construction companies for gardens way to work with up following, with purpose to see if there was an efficient and not resource demanded system which gave much value.